Epidemic as History: Interplay of Structure and Agency in Narratives of the Black Death in Contemporary Textbooks for Russian Language Schools - Fabrykant, Marharyta (Voprosy obrazovaniya / Educational Studies Moscow, 2021)
The article presents the results of a comparative analysis of narratives of the Вlack Death (the epidemic of plague that struck Western Europe in the mid-1300s) in six contemporary history textbooks in the Russian language published in Russia, Belarus, Ukraine, and Kazakhstan. Structural narrative analysis provides an answer to the research question about the interplay of external circumstances (structure) and individual choices (agency) in depicting the causes of the Black Death, its course of events, and attribution of its developments and consequences. Findings demonstrate that structure prevails over agency. The textbooks offer no behavioral patterns to internalize and implicitly conceptualize behavior in an epidemic as a mass phenomenon, not as a product of many individual choices. This perception of agency blatantly contradicts the two prerequisites for an effective epidemic response elaborated during the COVID-19 pandemic: quality of governance and population’s willingness to comply with authorities’ recommendations in spite of the growing circulation of false information. The Black Death is presented in textbooks as an inevitable attribute of the Middle Ages — the “era of calamities”. Hence, an epidemic in any other historical period appears an omen of “bad times” coming, which is likely to create expectations of new unavoidable disasters and foster catastrophic perceptions of the already existing problems. To shift this approach to history as “life’s teacher”, intrinsic to didactic pedagogy, two methods are suggested: explicit comparison with epidemics from other historical periods (not only the present) and counterfactual thinking to create alternative scenarios with regard to general patterns of human behavior and the characteristics of the Medieval Period.